2006
DOI: 10.1111/j.1469-8986.2006.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the spontaneous presence of a spouse/partner and others on cardiovascular reactions to an acute psychological challenge

Abstract: The presence of supportive others has been associated with attenuated cardiovascular reactivity in the laboratory. The effects of the presence of a spouse and others in a more naturalistic setting have received little attention. Blood pressure and heart rate reactions to mental stress were recorded at home in 1028 married/partnered individuals. For 112 participants, their spouse/partner was present; for 78, at least one other person was present. Women tested with a spouse/partner present showed lower magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 73 publications
(116 reference statements)
2
21
1
Order By: Relevance
“…In contrast, another study found no main effect of sex of supporter (25). We have recently reported that women undergoing a mental stress test in their homes in the presence of their male partners showed attenuated reactions relative to men tested with their female partners present (26). Clearly, sex of supporter warrants further attention.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…In contrast, another study found no main effect of sex of supporter (25). We have recently reported that women undergoing a mental stress test in their homes in the presence of their male partners showed attenuated reactions relative to men tested with their female partners present (26). Clearly, sex of supporter warrants further attention.…”
Section: Introductionmentioning
confidence: 58%
“…However, it is possible that females feel less evaluated when support is provided by a male friend as this person is less similar to themselves than a female friend. Further, a previous study where women were tested either with or without the presence of their spouse/partner showed attenuated SBP and HR reactivity when their spouse/partner was present (26). Similarly, in response to the cold pressor test, participants tested with their spouse present were characterised by attenuated reactivity (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PASAT has been shown previously to reliably perturb both the cardiovascular system and salivary cortisol (Phillips et al, 2006Ring et al, 2002). Participants were presented with a series of single digit numbers by compact disc and required in each case to add the present number to the number previously presented and call out the answer.…”
Section: Acute Psychological Stress Taskmentioning
confidence: 99%